Framework Guidlines and Governance for Designing Local Adaptation Plan of Action to Mainstream Climate Smart Villages in India - Aryal, Jeetendra Prakash; Jat, Mangi Lal; Gehlawat SK; Agarwal, Tripti; Singh, Rajbir (2015)
Based on the extensive review of existing frameworks and practices on climate change adaptation and authors experiences in Indian context, this study presented BRIFFS (bottom-up, responsive, inclusive, flexible, forward-looking, and sustainable) as the major guidelines for developing LAPA. This study presented the major steps of LAPA with clear actions, activities and also tools that can be used in each step. The nine steps of LAPA are as follows: 1) Communicating climate change risks and adaptation measures at local level, 2) Assessment of climate risks and vulnerabilities and scoping of adaptation actions, 3) Prioritisation of adaptation options, 4) Formulation of LAPA, 5) LAPA integration in planning process, 6) Institutional arrangement to implement LAPA, 7) Implementation of LAPA, 8) Progress assessment of LAPA, and 9) Feedback and revision of LAPA.